Overexpressing the Myrosinase Gene TGG1 Enhances Stomatal Defense Against Pseudomonas syringae and Delays Flowering in Arabidopsis - Zhang, Kaixin; Su, Hongzhu; Zhou, Jianxin; Liang, Wenjie; Liu, Desheng; Li, Jing (Frontiers in Plant Science, 2019)
Myrosinase enzymes and their substrate glucosinolates provide a specific defensive mechanism against biotic invaders in the Brassicaceae family. In these plants, myrosinase hydrolyzes glucosinolates into diverse products, which can have direct antibiotic activity or function as signaling molecules that initiate a variety of defense reactions. A myrosinase, β-thioglucoside glucohydrolase 1 (TGG1) was previously found to be strikingly abundant in guard cells, and it is required for the abscisic acid (ABA) response of stomata. However, it remains unknown which particular physiological processes actually involve stomatal activity as modulated by TGG1. In this experimental study, a homologous TGG1 gene from broccoli (Brassica oleracea var. italica), BoTGG1, was overexpressed in Arabidopsis. The transgenic plants showed enhanced resistance against the bacterial pathogen Pseudomonas syringae pv. tomato (Pst) DC3000 via improved stomatal defense. Upon Pst DC3000 infection, overexpressing BoTGG1 accelerated stomatal closure and inhibited the reopening of stomata. Compared with the wild type, 35S::BoTGG1 was more sensitive to ABA- and salicylic acid (SA)-induced stomatal closure but was less sensitive to indole-3-acetic acid (IAA)-inhibited stomatal closure, thus indicating these hormone signaling pathways were possibly involved in stomatal defense regulated by TGG1. Furthermore, overexpression of BoTGG1 delayed flowering by promoting the expression of FLOWERING LOCUS C (FLC), which encodes a MADS-box transcription factor known as floral repressor. Taken together, our study’s results suggest glucosinolate metabolism mediated by TGG1 plays a role in plant stomatal defense against P. syringae and also modulates flowering time by affecting the FLC pathway.